NcRNAs in Vascular and Valvular Intercellular Communication - Bartsch, Benedikt; Goody, Philip Roger; Hosen, Mohammed Rabiul; Nehl, Denise; Mohammadi, Neda; Zietzer, Andreas; Düsing, Philip; Pfeifer, Alexander; Nickenig, Georg; Jansen, Felix (Frontiers in Molecular Biosciences, 2021)
Non-coding RNAs have been shown to be important biomarkers and mediators of many different disease entities, including cardiovascular (CV) diseases like atherosclerosis, aneurysms and valvulopathies. Growing evidence suggests a central role of ncRNAs as regulators of different pathological pathways involved in endothelial dysfunction, cardiovascular inflammation, cell differentiation and calcification. This review will discuss the role of protein-bound and extracellular vesicular-bound ncRNAs as biomarkers of vascular and valvular diseases, their role as intercellular communicators, and regulators of disease pathways and also highlights possible treatment strategies.